Lanthanide‐Catalyzed Reversible Alkynyl Exchange by Carbon–Carbon Single‐Bond Cleavage Assisted by a Secondary Amino Group. (11th August 2016) - Shao, Yinlin; Zhang, Fangjun; Zhang, Jie; Zhou, Xigeng
Abstract: Lanthanide‐catalyzed alkynyl exchange through C−C single‐bond cleavage assisted by a secondary amino group is reported. A lanthanide amido complex is proposed as a key intermediate, which undergoes unprecedented reversible β‐alkynyl elimination followed by alkynyl exchange and imine reinsertion. The in situ homo‐ and cross‐dimerization of the liberated alkyne can serve as an additional driving force to shift the metathesis equilibrium to completion. This reaction is formally complementary to conventional alkyne metathesis and allows the selective transformation of internal propargylamines into those bearing different substituents on the alkyne terminus in moderate to excellent yields under operationally simple reaction conditions.